Linking soil profile N2O concentration with surface flux in a cotton field under drip fertigation. (15th September 2021) - Li, Yanyan; Gao, Xiaopeng; Tenuta, Mario; Gui, Dongwei; Li, Xiangyi; Zeng, Fanjiang
Abstract: It remains unclear how the source and rate of nitrogen (N) fertilizers affect N2 O concentration and effluxes along the soil profile under the drip-fertigated agricultural system. A plot-based field study was performed in 2017 and 2018 in a cotton field in arid northwestern China, with an objective to elucidate the impact of the applications of conventional urea (Urea), polymer-coated urea (ESN) and stabilized urea (SuperU) at rates of 120 and 240 kg N ha −1 on concentration and efflux of N2 O in the soil profile and its relationship with N2 O surface emissions. The in-situ N2 O concentrations at soil depths of 5, 15, 30 and 60 cm were measured and used to estimate soil profile N2 O effluxes. Estimates of surface N2 O flux using the concentration gradient-based (GM) were compared with those measured using the chamber-based (CM) method. In both years, soil N2 O concentrations at all depths increased in response to basal N application at planting or in-season fertigation events. However, N rate or source did not affect soil N2 O concentrations or effluxes at each depth. Surface emissions of N2 O were mostly associated with that presented in the top layer of 0–15 cm. Surface N2 O efflux determined by GM was poorly or not associated with those of chamber measurements, which was attributed to the low N2 O production restricted by soil moisture condition under the drip-fertigated condition. These results highlight the challenge of applying the enhanced efficiency N fertilizer products in the drip-fertigated agricultural system. Graphical abstract: Image 1 Highlights: Soil N2 O effluxes were estimated based on profile N2 O concentrations. N source or rate did not affect soil profile N2 O concentration and efflux. Soil N2 O production in the 0–15 cm layer dominated surface emissions. Gradient-based N2 O effluxes decoupled with chamber measurements. Abstract : Use of enhanced efficiency N fertilizers did not affect N2 O concentration and efflux along the soil profile under the drip-fertigated system. Estimates of N2 O flux based on soil profile N2 O concentration gradients were in the same order of magnitude but higher, compared with measurement of the static chamber.